2019
DOI: 10.1002/nau.23912
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high impact crossfit exercises on stress urinary incontinence in physically active women

Abstract: Aims The impact of CrossFit (high energy and intensity exercise) on SUI has not been well described. This study evaluates the incidence of SUI in physically active women, and examines specific exercises that can increase SUI. Methods A cross‐sectional study was conducted in women from four CrossFit centers and one aerobic center for comparison. Participants were surveyed regarding baseline demographics, activity levels, severity, and frequency of leakage during CrossFit exercises as well as preventative strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
3
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 19 publications
6
39
3
15
Order By: Relevance
“…In the present study, no changes were observed in proportions or severity of UI across the first year of fitness club membership. Most women perceived the symptoms to be slight, and the prevalence of UI was lower than has been reported in the general female population [ 2 ] as well as other studies of women participating in different sports and exercise classes [ 8 , 15 , 16 ], including a study of young nulliparous women (20–25 years) attending gyms [ 14 ] and group fitness instructors [ 7 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, no changes were observed in proportions or severity of UI across the first year of fitness club membership. Most women perceived the symptoms to be slight, and the prevalence of UI was lower than has been reported in the general female population [ 2 ] as well as other studies of women participating in different sports and exercise classes [ 8 , 15 , 16 ], including a study of young nulliparous women (20–25 years) attending gyms [ 14 ] and group fitness instructors [ 7 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Much research has focused on UI in athletes, including group fitness instructors [ 7 , 8 , 13 ]. A few studies have also reported the prevalence of UI among regular exercisers, including young women who participate in high-impact and high-intensity exercise [ 14 16 ]. However, there is a lack of knowledge about beginner recreational exercisers in a fitness club setting.…”
Section: Introductionmentioning
confidence: 99%
“…The hammock hypothesis suggests that urinary symptoms, such as SUI, occur when the increase in abdominal pressure exceeds the threshold of the urinary sphincter [19–21]. This hypothesis also supports beliefs that SUI is related to muscle fatigue, evidenced by more frequent leakage later in the day and with more exercises [11].…”
Section: Altered Pelvic Floor In Response To Physical Activitymentioning
confidence: 57%
“…Increased intrabdominal pressure is thought to fatigue muscles of the pelvic floor as they balance forces. Therefore, when the downward force from the abdomen is not balanced by the upward force from the pelvic floor muscles, stress urinary continence can occur [11]. This is similar to the mechanism explaining how childbirth damages pelvic floor muscles, and therefore this process is often thought to be the cause of SUI among nulliparous females [2].…”
Section: Altered Pelvic Floor In Response To Physical Activitymentioning
confidence: 99%
“…Recent studies have shown that the prevalence of UI in CrossFit practitioners is around 30%, with skipping rope the most related to this event [6,7]. The etiopathogenesis of this condition is related to the increase in intra-abdominal pressure that is not balanced by the contraction of the pelvic muscles [8].…”
Section: Introductionmentioning
confidence: 99%